PEMBERDAYAAN PENDIDIKAN KARAKTER DAN BAHASA PADA REMAJA DALAM KELUARGA - Replita, Replita (IAIN Padangsidimpuan, 2014)
Family education can form character of children in mental of religion. Thus, from time side, teaching based character is longlife education. It is often out from our control and we think education to children is just authority of the legal school and the teachers. It means, children are dominated by logic than behavior or character.